Medicinal plant compounds as natural food preservatives: a review - Husain, Saiyyad Alamdar; Farheen, S Rabia; Husain, Murad (Journal of Postharvest Technology, 2022)
Natural compounds, such as medicinal plant essential oils and extracts, have been widely examined for their antibacterial capabilities, with promising results. The potential for natural preservatives to replace synthetic preservatives has been established by looking at the effects of thyme, basil, oregano, and rosemary extracts on food products. This review offers readers the chance to learn about recent developments in the antibacterial and antioxidant properties of natural chemicals that are important to the contemporary food industry. In addition to contributing to more effective environmental preservation when chemicals are substituted with natural substances, their prospective usage in food production could result in the production of safer and healthier foods.